2012
DOI: 10.1177/0218492311435154
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion barrier reduces postoperative adhesions after cardiac surgery

Abstract: Reoperation in cardiac surgery is associated with increased risk due to surgical adhesions. Application of a bioresorbable material could theoretically reduce adhesions and allow later development of a free dissection plane for cardiac reoperation. Twenty-one patients in whom a bioresorbable hyaluronic acid-carboxymethylcellulose adhesion barrier had been applied in a preceding surgery underwent reoperations, while 23 patients underwent reoperations during the same period without a prior adhesion barrier. Blin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…The study demonstrated a reduction in tenacity score, the extent of the adhesions and duration of the operation. More recently, Kaneko et al [26] demonstrated similar results. However, in the aforementioned study, some of the patients in hyaluronic acid membrane group had the pericardium left open, some closed and some augmented with ePTFE membrane.…”
Section: Discussionmentioning
confidence: 64%
“…The study demonstrated a reduction in tenacity score, the extent of the adhesions and duration of the operation. More recently, Kaneko et al [26] demonstrated similar results. However, in the aforementioned study, some of the patients in hyaluronic acid membrane group had the pericardium left open, some closed and some augmented with ePTFE membrane.…”
Section: Discussionmentioning
confidence: 64%
“…A recent report by Kaneko et al compared 22 patients who underwent cardiac reoperation after Seprafilm® application during the previous surgery with 23 patients reoperated without application of an adhesion barrier. The surgical adhesions were graded prospectively from video recordings during reoperation: they were less tenacious if Seprafilm® had been used [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…This solid adhesion barrier limited the formation of cardiac retrosternal adhesions in pigs [ 82 ]. Seprafilm® has also been proven to be safe in cardiac surgery and to reduce the formation of adhesions [ 83 , 84 ]. Another barrier that consists of a collagen membrane is COVA™ CARD.…”
Section: Battling Adhesionsmentioning
confidence: 99%